Performance of hydroxyapatite coatings electrodeposited on micro-arc oxidized magnesium alloys using a static magnetic field. Issue 19 (2nd February 2015) - Xu, Quan; Liu, Yao; Liu, Chuangwei; Tian, Ang; Shi, Xiaoguo; Dong, Chenbo; Zhou, Ying; Zhou, Hongjun
Abstract : Fabrication and investigation of the biocompatibility of hydroxyapatite coating electrodeposited on micro-arc oxidized magnesium alloys via a static magnetic field. Abstract : Biodegradable magnesium (Mg) and its alloy are some of the most widely used functional materials for osteosynthetic applications due to their rapid degradation properties, and thus they do not require surgical removal. However, the rapid degradation of magnesium alloy can cause a high alloy corrosion rate, which needs to be regulated during the bone healing process. In this study, we coated hydroxyapatite (HA) crystal nanostructures on magnesium alloy by an electrodeposition process in the presence of a static magnetic field to inhibit corrosion. The physical and chemical properties of the HA coatings were characterized using SEM, XRD, EDS, as well as a corrosion test. In addition, the interaction between HA coatings and osteoblast cell regulated cellular behavior was investigated. The result indicated that the corrosion resistance ability of the magnesium alloy coated with HA was significantly improved compared with the uncoated magnesium alloy. An initial corrosion potential of Ca–P composite coating at −0.5 V was achieved, which is almost one third of the potential value of the pure magnesium alloy (AZ91D). The proliferation, adhesion and expression analysis of IGF-1 protein indicated that the HA nanocrystals could enhance the viability of the cells. This work provides insight into the development of the next generation of biocompatible alloys for biomedical applications.